2020
DOI: 10.2139/ssrn.3669498
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Mental Health Disruptions During Covid-19

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In those times of relative stability, research had additionally demonstrated the higher prevalence of mental health issues amongst the PhD student population across research disciplines, as compared to other students within academia [ 9 ] and the general population [ 9 , 11 , 12 ]. In the period since Covid-19 disrupted our social and economic lives, depression levels in the general population have been exacerbated globally [ 13 , 14 ]. These trends suggested that the already high prevalence of poor mental health in PhD students is likely to be further exacerbated during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In those times of relative stability, research had additionally demonstrated the higher prevalence of mental health issues amongst the PhD student population across research disciplines, as compared to other students within academia [ 9 ] and the general population [ 9 , 11 , 12 ]. In the period since Covid-19 disrupted our social and economic lives, depression levels in the general population have been exacerbated globally [ 13 , 14 ]. These trends suggested that the already high prevalence of poor mental health in PhD students is likely to be further exacerbated during the pandemic.…”
Section: Introductionmentioning
confidence: 99%